Dataset for waste tire and constituent polymers pyrolysis on Me/NT-Ti (Me = Pd, Au, Pt) - Arteaga Pérez, Luis E. (2021)
This dataset includes results on the thermal characterization of waste tires by thermogravimetric analysis. In addition here we report a complete dataset on the analytical pyrolysis (Py-GC/MS) experiments of WT in the presence of different catalysts. The data is complementary to a published paper, thus a complete description of the materials, methods and equipments used to obtain this dataset is provided in those papers. The experiments were done for waste tires coming from light vehicles, and three metals Pd, Pt, Au deposited on titanate nanotubes (NT-Ti) were used as catalysts for selectively produce valuable chemicals. Experimental factors were the metal nature of the catalyst and the pyrolysis temperature (400 – 450ºC). Moreover, the pyrolysis was investigated for three individual polymers (polyisoprene, butadiene, and styrene-butadiene) to establish possible reaction routes describing the role of metals in the pyrolysis reaction map and product distribution. Three folders are provided here: 1- Raw datafile for TGA of WT recorded in N2 flow between 20 and 650ºC at 10 ºC/min. 2- Datafiles for TurboMass software v5.4 (Perkin Elmer, 2017) with the results of all pyrolytic experiments ordered by materials, temperatures and catalysts nature. 3- Excel files with the retention time, peak area, peak height, among other chromatographic results from the Py-GC/MS.